UPAYA KOREA SELATAN DALAM MENINGKATKAN KUNJUNGAN WISATAWAN MANCANEGARA KE KOREA SELATAN MELALUI OPENING CEREMONY PYEONGCHANG WINTER OLYMPIC 2018 - Muhammad Gibran Fajarohman Winarno; Syafri Harto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Tuorism is one of aspect to make a nation grow and can be positif impact for a nation, because of that reason many nation want to promote their tourism aspect and in this reasearch will describe South Korea as a nation to increase tourism aspect. South Korea Effort to increase tourism aspect trough sports olympic, the aim of this effort is to promote South Korea culture at the opening ceremony winter olympic 2018 in Pyeongchang that will show Korean traditional culture to attract people and make them think that South Korea haved beautyfull culture and that can make them comeback to Korea for vacation. The Researcher collect data from Journal,books,official website of international organization and official goverment,and website of mass media and use constructivism prespective combine with culture diplomacy theory to analyze South Korea effort to promote that they haved rich traditional culture for attarct foreign touris with opening ceremony of Pyeongchang winter olympic 2018 . Result of this reasearch show that South Korea effort to increase foreign tourism use opening ceremony Pyeongchang winter olympic 2018 to attract foreign tourism by cultural peformances of Korean traditional clothes,dance, Korean singer to promote K-pop and show peace aspect with North Korea. Key Words : South Korea,Pyeongchang winter olympic,IOC,Traditional culture,Tourism.